(untitled) (JED (Jurnal Etika Demokrasi), 2023)
This study aims to analyze and describe local wisdom in the form of the traditional game Pacu Tabang Duck along with Pancasila values that can be explored in it, amidst the onslaught of dynamics of global issues. Pacu tabang ducks is a typical tradition of Luak fifty which consists of the district of fifty cities and the city of Payakumbuh. This study used a qualitative design with a descriptive method. Research data were collected through observation, in-depth interviews and documentation studies. The research findings show that (1) the tradition of spurring tabang itiak is a hereditary tradition in the luak fifty community; (2) the existence of the pacu tabang itiak tradition can be maintained because of the Pancasila values contained therein. The implementation of the duck racing tradition is not only a tradition of the local community but through local government policy, this tradition has become a tourist calendar event for the fifty cities and towns of Payakumbuh so that it attracts tourists to attend and witness it every year. The implementation of the Pacu Tabang Duck tradition brings economic blessings to the local community because of the large number of tourists who attend.